Identification of Wind-Induced Particle Resuspension in Urban Environment Using CFD Modelling - Jakub Linda; Jiří Pospíšil; Klaudia Köbölová (Atmosphere, 2022)
Air pollution caused by particulate matter (PM) is a current problem in many cities. With the introduction of strict emission limits and electric cars, lower particle production is expected in the future. However, there are sources of particles that cannot be easily influenced. These include resuspension, where particles deposited on surfaces re-enter the air, causing pollution multiple times. Resuspension can account for up to 18% of the total emissions in some cases. The present paper focuses on the use of the computational fluid dynamics (CFD) tools to describe the flow in a street canyon where resuspension by wind occurs. Based on the calculated flow, a resuspension model is applied to see where resuspension occurs and how far the particles can travel. The shear stresses on the surfaces and the character of the flow field in the boundary layer are evaluated. Different building configurations and flow parameters are tested using a simple 2D model. The model makes it possible to see in which parts of the street canyon resuspension can occur. It shows that the particles leave the street canyon only from the surfaces where the conditions are suitable for resuspension. These particles then enter the mainstream. However, most of the particles stay in the canyon, which can cause resuspension to pollute the air repeatedly. This effect can have a severe impact on human health. The total dispersion of particles in the urban environment is evaluated. The results may be useful for cities that clean the streets, as it is clear which areas will benefit most from the cleaning.